Continuous kidney replacement therapy with CARPEDIEM® of premature and low birth weight neonates from the French registry - Battista, Jennifer; Trolli, Sergio Eleni dit; Ranchin, Bruno; Bacchetta, Justine; Baleine, Julien Frederic; De Luca, Danièle; Decramer, Stéphane; Enoch, Carole; Faudeux, Camille; Fila, Marc; Regiroli, Giulia; Schmitt, Claus P.; et al. (Pediatric nephrology, 2025)
Background: Acute kidney injury (AKI) affects 30% of hospitalized pediatric patients, with high mortality in neonates. The Cardio-Renal Pediatric Dialysis Emergency Machine® (CARPEDIEM®) is a continuous kidney replacement therapy (CKRT) device designed for infants weighing 2.5–9.9 kg. Methods: We retrospectively evaluated the technical feasibility, efficacy regarding solute and fluid removal, tolerability and patient outcomes of CKRT with CARPEDIEM® in preterm and low birth weight (LBW) neonates (< 2.5 kg) with AKI, treated in six French pediatric intensive care units. Results: Ten neonates with a median gestational age of 31 [interquartile 29–32] (range 25–38) weeks and a birth weight of 1.1 [IQ 1.0–1.7] (0.6–2.0) kilograms received continuous veno-venous hemofiltration (CVVH) during 22 sessions. CVVH was initiated at a median age of 6 [2–12] (1–72) days and a weight of 1.9 [1.5–2.4] (1.3–2.8) kg. All CVVH sessions achieved efficient blood purification. At CVVH initiation fluid overload was 29 [21–39] (11–68)% and improved until the end of treatment to 16[8–18] (0–40)% (p = 0.04). Thrombocytopenia, requiring platelet transfusion, and hypotensive episodes were the main complications observed in 14 and 13 sessions. No deaths occurred during the CARPEDIEM® treatment but all except one neonate died 6 [1–9] (1–63) days later, mainly due to multi-organ failure or ethical considerations linked to severe brain injury. Conclusion: CVVH using CARPEDIEM® is technically feasible and effective in neonates with a birth weight below 2.5 kg with AKI and multi-organ dysfunction with the potential to improve clinical management. Further studies are needed to define adequate timing, dosing, and the impact on patient outcome.
Veröffentlicht: 16. Juli 2025
Gesehen am 26.11.2025